Management of Epulis Fissuratum of Mandibular Anterior Region By Maintaining The Vestibular Depth. A Case Report - KHUDA -; SHAFQAT HUSSAIN; KAPIL KUMAR; OSAMA SHAIKH; IFTIKHAR AHSEN (Gandhara University, 2022)
OBJECTIVES Epulis Fissuratum or Denture-induced hyperplasia is benign tumor-like hyperplasia of fibrous connective tissue, which develops usually in association with an ill-fitting complete or partial denture.  The aim of this report is to present a case showing the treatment of Epulis fissuratum in relation to an ill-fitting denture with a Simple but innovative technique. The epulis was removed with the conventional surgical approach in which the excision of the epulis was carried out by a split-thickness flap approach in which the wound healing is achieved by secondary closure. The existing denture was relined with a soft tissue conditioner to maintain the depth of the vestibule by preventing the post-surgical wound contracture during healing and to prevent further surgery for vestibulopathy. In addition, the patient continued using the existing denture for functional and aesthetic purposes. After two weeks of wound healing, the vestibular depth was maintained by the relined existing denture. Then the new dentures were fabricated accordingly. After one month of follow-up, no signs of recurrence of epulis fissuratum were noticed.